2010
DOI: 10.1111/j.1600-0536.2009.01668.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends of preservative allergy in Denmark (1985–2008)

Abstract: Dillarstone's prediction was confirmed as the prevalence of contact allergy to individual preservatives remained relatively stable. However, the overall burden of preservative allergy seemed to increase. Introduction of new preservatives may add to the burden of contact allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
2
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 27 publications
8
77
2
7
Order By: Relevance
“…La MCI y la MI, al igual que otros conservantes del grupo formaldehído o mercuriales, pueden tener alto poder de sensibilización, como se ha demostrado por estudios experimentales y por la practica clínica, presentando la MCI mayor poder sensibilizante que la MI 12 . Actualmente constituye una de las causas más frecuente de alergia de contacto por preservativos [14][15][16] . Asimismo, además de la MCI y MI existen otras isotiazolinas disponibles para la producción de productos industriales, en particular, la benzisotiazolinona, que se utiliza con frecuencia en la pintura, pudiendo ser responsable de reacciones cruzadas con MCI/MI 17 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La MCI y la MI, al igual que otros conservantes del grupo formaldehído o mercuriales, pueden tener alto poder de sensibilización, como se ha demostrado por estudios experimentales y por la practica clínica, presentando la MCI mayor poder sensibilizante que la MI 12 . Actualmente constituye una de las causas más frecuente de alergia de contacto por preservativos [14][15][16] . Asimismo, además de la MCI y MI existen otras isotiazolinas disponibles para la producción de productos industriales, en particular, la benzisotiazolinona, que se utiliza con frecuencia en la pintura, pudiendo ser responsable de reacciones cruzadas con MCI/MI 17 .…”
Section: Discussionunclassified
“…La concentración de MCI/MI en productos cosméticos ha estado regulada desde los años 80, sin embargo sin presentar impacto en la prevalencia de su sensibilización en la población general 16,18 . Bajo la legislación actual la concentración máxima de Kathon CG es de 15 ppm en todos los cosméticos en la Comunidad Europea, mientras que en los EEUU se establece como concentración máxima para los preparados rinse-off 15ppm y para los leave-on 7,5 ppm 19,20 , siendo estas las recomendaciones del fabricante 21. .…”
Section: Discussionunclassified
“…While the overall prevalence of preservative contact allergy remains frequent in many EU member states, two Danish studies have shown that the overall prevalence and burden of preservative contact allergy is increasing every time a new preservative is marketed [6][7][8][9]. This has clearly been exemplified by the introduction of MI into the European cosmetic market in 2005 where MI was given a positive opinion by the SCCS and entered onto Annex V as a preservative allowed for use in cosmetic products.…”
Section: Temporal Trend Of Contact Allergy To Preservativesmentioning
confidence: 99%
“…Notwithstanding recent epidemics of contact allergy to single (troublesome) preservatives, the overall prevalence of contact allergy is maintained at alarmingly high levels above 10% in consecutive patch-tested dermatitis patients [6][7][8][9]. The former comprehensive observational study by Wilkinson et al showed that in 80,000 European patients from 11 European centers, stable and high levels of contact allergy to the "old and prior epidemic" preservatives (formaldehyde, formaldehyde releasers and MCI/MI) were observed [9].…”
Section: Temporal Trend Of Contact Allergy To Preservativesmentioning
confidence: 99%
See 1 more Smart Citation